Estudo dos fatores que afetam a produtividade em canteiros de obra de empresas brasileiras - Maciel, Amanda Patricia (2022)
The construction industry plays an important role in the economy of any country. Its economic growth and sustainable development are mainly determined by productivity. Productivity has a significant impact on the efficiency of companies and is the key to greater competitiveness of organizations. Therefore, the objective of this research is to analyze the productivity factors of construction sites located in the South and Southeast of Brazil. For this, the Survey was used as a research strategy, in which, through a questionnaire, information was collected from 78 construction sites in the South and Southeast regions of Brazil. The data obtained were analyzed using Factor Analysis, calculating the Relative Importance Index and Descriptive Analysis. The results demonstrate that design changes are the main difficulty faced in the works. In addition, they show that the groups related to manpower, resources, management efficiency and rework are the ones that stand out as the most significant for productivity. The factors considered less important are those related to outsourcing, security, customers and sustainability actions. As for the diagnosis of factors, most of the items were evaluated with a tendency to be carried out at construction sites, pointing out that constructions generally perform their activities efficiently. However, three factors presented negative results, which are: the high workload of the person responsible for the work, the low availability of qualified labor in the market and the low amount of sustainability actions, indicating problems present in the civil construction sector. With the results of these analyses, it is possible to expand knowledge about productivity in the study region, making it possible to discuss ways to improve the performance and management of construction sites, bringing results that collaborate both with the theoretical knowledge of the subject and for the responsible for building management.